A study on indoor air quality monitoring system - Gan, Lee Eng (2016)
Singapore is facing the annual haze pollution, one of the biggest issue to be solve periodically. Severe smoke haze due to forest fires from his neighbour country, Indonesia that harming human’s health. Most of the public only considering on the outdoor air quality or Pollutant Standards Index (PSI) published by National Environment Agency (NEA). We often missed out the indoor air quality (IAQ) effect that significantly associate with our health. In fact, by considering the amount of time many of us spend in the buildings, indoor air quality law is an area we shouldn’t take for granted instead must pay concern on. Looking at Singapore building environment, this hot and humid climate little red dot are surrounded by buildings are mostly installed with air-conditioning system in order to achieve thermally comfortable level. However, a more precise value of IAQ of air-conditioned room and its’ effect are yet to be focused. In this Final Year Project, IAQ case study conducted in (i) condominium vs terrace house and (ii) air-conditioned vs non-air-conditioned environment at residential and office area. An IAQ monitoring system was installed to establish valuable real-time IAQ profile at various locations. In this paper, the focus of air pollutants collected are: carbon dioxide, volatile organic compounds, PM2.5, temperature and humidity. Qualified recorded readings being analysed and compared with allowable concentration following standard guidelines provided by government.